Defenserelated gene expression in susceptible and tolerant bananas (Musa spp.) following inoculation with nonpathogenic Fusarium oxysporum endophytes and challenge with Radopholus similis - Paparu, P.; Dubois, T.; Coyne, Danny L.; Viljoen, Altus (Elsevier, 2007)
Radopholus similisis a major pest of East African highland cooking bananas (Musaspp.) in Uganda. Non-pathogenic Fusariumoxysporumendophytes, isolated from bananas in farmers’ fields, have shown potential to reduceR. Similis numbers in tissue culture banana. The mechanism through which endophytes confer resistance to nematodes has previously been demonstrated to involve inducedresistance. In this study, the expression of eight defense-related genes in banana was investigated using quantitative real-time reverse transcription PCR. Plants of susceptible (cv. Nabusa, genomic group AAA-EA) and tolerant (cv. Kayinja, genomic group ABB) banana cultivars were inoculated with endophyticF. Oxysporum strain V5w2. Gene expression levels were analysed following endophyte inoculation and nematode challenge. Endophyte colonization of roots of the tolerant cultivar induced transient expression of POX and suppressed expression ofPR-3,lectin, PAE, PALandPIR7A. CatalaseandPR-1activities were up-regulated in the tolerant cultivar 33days after endophyte colonization of roots, but their expressions were further up-regulated following nematode challenge. Apart from POX andlectin, the other genes analysed were not responsive to endophyte colonization orR. Similis challenge in the susceptible cv.Nabusa. This is the first report of endophyte-induced defense-related gene expression in banana.